CUT-OFF POINT OF PSA AND PSA DENSITY IN PROSTATE CANCER SUSPECTED PATIENTS - Simanjuntak, Daniel; Safriadi, Ferry (Indonesian Journal of Urology, 2016)
Objective: In Hasan Sadikin General Hospital Bandung prostate biopsy is recommended for patients with prostate specific antigen (PSA) levels above 10 ng/mL or PSA density (PSAD) above 0.15 if PSA in between 4–10 ng/mL. However, there were other factors beside of prostate cancer (PCa) that could influence PSA value, such as racial differences and prostatitis. Thus, the optimal cut-off point for PSA is still debatable in national level. This research aimed to determine PSA and PSAD cut-off point for patient suspected of PCa in Hasan Sadikin Hospital Bandung. Material & Methods: A total of 502 patients underwent prostate biopsy for suspicion PCa from 2010–2014. The cut-off point of PSA and PSAD is generated from receiver operating characteristic (ROC) curve. Results: The cut-off point for PSA was 14.6 ng/mL (sensitivity 81.4%, specificity 29.8%). The cut-off point for PSAD was 0.23 (sensitivity 81.4%, specificity 34.8%). Positive predictive value (PPV) for this new cut-off point of PSA and PSAD were 41.1% and 37.6% respectively. Conclusion: PSA and PSAD cut-off point for patients in our center was 14.6 ng/mL and 0.23 respectively. This value is relatively higher compared to the Indonesian consensus. The difference might occur due to high rate of urinary tract infection in patients attending Hasan Sadikin General Hospital Bandung.